Karakterisasi Fisiko-Kimia Biji dan Kulit Ari Kacang Bogor Asal Jampang-Sukabumi Jawa Barat - Rizki Maryam Astuti; Nurheni Sri Palupi; Maggy Thenawidjaja Suhartono; Hanifah Nuryani Lioe; Eni Kusumaningtyas; Laras Cempaka (Jurnal Teknologi dan Industri Pangan, 2022)
The traditional cultivation and limited use of bambara groundnut (Vigna subterranea) seed and coat have encouraged the development of this commodity. The aim of this research was to characterize the seed and coat of bambara groundnut from Jampang, Kab. Sukabumi, West Java. Analysis on bambara groundnut seed including proximate analysis, in vitro protein digestibility, starch content, and dietary fiber, as well as analysis on its coat including anthocyanin, total phenolic, antioxidant activity, phytic acid and tannin, were examined in this study. The results showed that bambara groundnut seed from Jampang-Sukabumi contained 16.53% proteins, 3.04% ash, 7.83% fats and 55.22% carbohydrates in dry basis (db). The carbohydrates consisted of starch 52.71% and dietary fiber 7.47% (db). The protein had an in vitro protein digestibility of 41.65% db. The purple seed coat contained of 1.51% anthocyanin, 25.85 mg/g total phenolic content (as gallic acid equivalent), antioxidant activity at 82.75% inhibition of free radical DPPH, 6.37 mg/g phytic acid, and 96.79 mg/g tannin (as tannic acid equivalent) in dry basis. The relatively high content of tannin and antioxidant activity but very low phytic acid content, make the bambara seed coat a potential source for tannin, meanwhile the bambara groundnut is potential as a nutrition source.